Effect of hall current in thermoelastic materials with double porosity structure - Kumar, R..; Vohra, R. (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation is concerned with one dimensional problem in a homogeneous, isotropic thermoelastic medium with double porosity structure in the presence of Hall currents subjected to thermomechanical sources. A state space approach has been applied to investigate the problem. As an application of the approach, normal force and thermal source have been taken to illustrate the utility of the approach.
Keywords: Hall currents; double porosity; thermoelasticity; state space approach; thermomechanical sources